ANALISIS KOMODITAS PERTANIAN UNGGULAN UNTUK MENDUKUNG KETERSEDIAAN PANGAN DI DAERAH ISTIMEWA YOGYAKARTA - , MARIA RATRI WULANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims is to determine the state of food security in the province of Yogyakarta and to find out the potency of districts/cities to produce the leading agricultural commodities such as carbohydrates, proteins and vitamins in food availability fulfillment. The method used is a descriptive method using secondary data population, GDP, food commodity production data sources of carbohydrates, vegetable protein source, eggs, poultry, meat of the animals, fish, vegetables and fruits at the district/city and DIY province in 2006-2011. Calculation is done with the LQ formula and total shift (shiftshare). Based on the research it was found that the ratio of food availability and consumption of normative showed that DIY had a surplus of cereals in all districts, except in the city of Yogyakarta. Bantul district, Gunungkidul district, Sleman and Kulon Progo Regency has the potential to produce commodities of food sources of carbohydrates, protein and vitamins in food availability fulfillment. Furthermore, there was no particular specialization and centralization of certain commodities in the agriculture commodities DIY on the food source of carbohydrates, protein and vitamins.